TaRL: The Potential and the Challenges in Learning Process at the Elementary School Parepare - Nur Asiza; Arif Rahman; Muhammad Irwan (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
TaRL is a learning approach that refers to the level of achievement or ability of students. This learning approach does not refer to the grade level. Learning is made according to the achievements, ability levels, needs of students, to achieve the expected learning outcomes. The researchers used Qualitative with descriptive approach. This research was located in SDN 3 Parepare and SDN 4 Parepare, the data collection was observation, interview and documentation. The aims of this research are potential and challenge of TaRL approach in Elementary School Parepare, therefore the main data source of this research is the teacher because the research wants to know their perception about TaRL approach in the learning process. The researcher used triangulation to validity test in this research. The result showed teaching at the right level, especially at SD Negeri 3 Parepare and SD 4 Parepare only a few implements it because the Merdeka curriculum has not been implemented in schools but indirectly the teaching at the right level approach the teachers have implemented it both in SD Negeri 3 and SD Negeri 4 Parepare. TaRL assists teachers in adjusting the level of student abilities so that learning in schools, especially in the classroom can run according to its objectives and teachers can find out the level of competence of each student through this approach so that teachers adjust the strategies, methods, approaches they take in the learning process.